PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE SNOWBALL THROWING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATA PELAJARAN IPS KELAS VI DI SD NEGERI 022 SINTONG KECAMATAN TANAH PUTIH - Azlan '; Makhdalena '; Hendripides ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The background of research study is that the learning outcomes of students categiruzed IPS is still low because students are still difficulties in accepting the lesson, the student are less active in learning, the teacher is less engaging students in learning and teachers only use the lecture method,and student are less involved directly to determine their own knowledge holds. Of these problems need to be a Class Action Research (PTK) by applying the learning mode cooperative mode throwing snowball . this research aims to improve learning outcomes IPS grade VI SDN 022 districts Sintong white ground with a number of students as many as 20 students. This research was conducted in two cycle by with one daily testa. Data collection instruments in reseach is observation sheet and test results of learning.The results of the data analysis of teachers in the first cycle of 78.12% second cycle increased to 90.62%. While the results of the data analysis activities of students in the first cycle 71.87. In the second cycle increased to 93.75%. From the results of this study showed that student learning has increased average student learning outcomes base score is 63.50 increased in the first cycle to 71.50 increase again in the second cycle is 85.25. To complete learn the basic score is 7 (35%) increased in the first cycle to 12 people (60%) increased again in the second cycle to 19 people (95%). Thus we can conclude that if applied Model pembelajaan Cooperative mode Snowball Throwing can improve learning outcomes VI IPS graders of SDN 022 districts Sintong white groundKey Words: Model Cooperatif Learning Type Snowball Throwing Student Achiement of science Studies2